2014
DOI: 10.1037/a0037032
|View full text |Cite
|
Sign up to set email alerts
|

Reinjury anxiety, coping, and return-to-sport outcomes: A multiple mediation analysis.

Abstract: Future avenues of research that aim to provide a greater knowledge and understanding of the relationship between reinjury anxiety and return-to-sport outcomes are discussed, including the need for alternative theoretical perspectives and diverse methodologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 45 publications
1
21
0
2
Order By: Relevance
“…While the majority have focused on quantitative outcomes, there are several studies that emphasize the importance of psychological factors in a patient's decision to return to sport. 39,[49][50][51] The patientderived themes from this study of patients with FAI also support this phenomenon.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…While the majority have focused on quantitative outcomes, there are several studies that emphasize the importance of psychological factors in a patient's decision to return to sport. 39,[49][50][51] The patientderived themes from this study of patients with FAI also support this phenomenon.…”
Section: Discussionsupporting
confidence: 60%
“…The most satisfying correlation was between coping mechanisms and specific patient responses on their individual pathway to return to sport. The use of adaptive coping mechanisms and positive reframing techniques allowed some patients to overcome obstacles of fear and promote internal motivators, 11,51 while maladaptive copers trended toward the inability to return to sport. Ivarsson et al 23 used the Brief COPE score on a series of Swedish soccer players and found that positive coping mechanisms contributed to overall mental well-being postinjury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also places a huge financial burden on the healthcare system, with estimated hospital costs of over A$75 million (e45 million) per year in Australia alone (Janssen et al, 2011). Perhaps not surprisingly, therefore, the increased incidence of ACL injuries over the last 20 years (Herzog et al, 2017) has been marked by a concomitant rise in the research attention afforded to factors associated with improving ACL outcomes-including those of a psychosocial nature (e.g., Brewer, 2010;Wadey et al, 2014;Ardern et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, fear of reinjury has been considered the most salient concern for athletes returning to sport post injury (Podlog, Dimmock, & Miller, 2011;Wadey, Podlog, Hall, Hamson-Utley, Hicks-Little, & Hammer, 2014).…”
Section: Fear Of Injurymentioning
confidence: 99%